2004
DOI: 10.1021/jp0457904
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Modification and Moisture on the Rates of Charge Transfer between Metals and Organic Materials

Abstract: This report is a study of the kinetics of contact charging resulting from the rolling of millimeter-sized metallic spheres on flat surfaces of polystyrene (PS). Charging was studied (i) for different values of the relative humidity (RH) of the air in contact with the system, (ii) in acidic and basic atmospheres, and (iii) for a series of PS surfaces oxidized to different degrees. The rates of charging increased with increasing RH; they were higher in basic atmospheres than in neutral or acidic ones and correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 35 publications
(85 reference statements)
3
83
1
1
Order By: Relevance
“…65 SPD of tribocharged surfaces has also been studied on PE, PTFE, and PET contacted by a bead of mercury and on PTFE, nylon, and aluminum rubbed with paper. 42,66 Oppositely charged domains on the surface of poly(oxymethylene), which are stable in time, were reported in Ref.…”
Section: B Related Literature Resultsmentioning
confidence: 99%
“…65 SPD of tribocharged surfaces has also been studied on PE, PTFE, and PET contacted by a bead of mercury and on PTFE, nylon, and aluminum rubbed with paper. 42,66 Oppositely charged domains on the surface of poly(oxymethylene), which are stable in time, were reported in Ref.…”
Section: B Related Literature Resultsmentioning
confidence: 99%
“…2 We still do not fully understand how and why such charge generation occurs, 3,4 although considerable progress has been made, such as by considering the role of mechanochemistry 6,7 and the difference of the composite between the surface and the bulk, 2,4,5,8 to more closely reveal the CE charging mechanism. Many researchers have suggested that moisture adsorbed on the surface plays a role in CE 9 and the related ambient humidity is also thought to be particularly important for surface charging. 10 McCarty and Whitesides reported a study on the CE of ionic electrets, in which they elaborated on the role of water in CE and proposed a mechanism based on the theory of the electric double layer to explain charge transfer under ambient environments with different humidity levels.…”
Section: Introductionmentioning
confidence: 99%
“…12 Much work has investigated the effect of ambient RH once. 9,10,[13][14][15][16][17][18] However, existing studies significantly disagree about the effect of RH on CE: some results show that CE increases with increasing RH, 9 others show that CE decreases as RH is increased, [14][15][16][17] and more still state as RH increases, CE increases at lower RH, followed by decreases at higher RH. 18 In addition, the results of Refs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, higher oxidation of polystyrene leads to lower contact angle (thus higher wettability) and determines the rate of charging (with the tribo-pairs formed by metals and organics) [81]. Other experiments confirm this relation by treating the surface with UV light to cause the contact angle change and then investigating the charging behavior [86].…”
Section: Humidity and Aciditymentioning
confidence: 95%
“…that the general trend of how tribo-charging is affected by this humidity-and acidity-introduced layer is not reached consensus yet [81][82][83].…”
Section: Humidity and Aciditymentioning
confidence: 99%